Optimalisasi Strategi Keberhasilan Pemberdayaan Desa Melalui Kegiatan Kirab Budaya dalam Peringatan Haul Simbah Wali Hasan bin Abu Hamid di Desa Magersari Kecamatan Patebon Kabupaten Kendal - Amar Prawijo; Muhammad Fatihuddin; Fahmi Uyunirrizqi; Navila Ziqni Molinda; Najah Farahulhusna; Ayudia Puspita Wati; Aulia Nur Anggita Putri (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Village empowerment in the Simbah Wali Hasan bin Abu Hamid cultural carnival and haul event in Magersari Village is one way of empowering the community in the aspects of participation, preserving traditions and strengthening community values. The cultural carnival is an effort to preserve traditions by integrating religious and local cultural aspects. Haul Simbah Wali Hasan bin Abu Hamid in Magersari Village, which is an annual commemoration of the death of this spiritual figure, is held every year on 24-25 Muharram, with this year being the 40th anniversary. On the first day, the event began with a lively cultural carnival, attended by the community enthusiastically. They paraded carrying tumpengan, gunungan, snacks and agricultural products, wearing traditional Javanese clothing, which shows their importance to the local community. This research uses a descriptive qualitative method with a direct case study in Magersari village. The findings show that cultural carnivals and hauls play an important role in maintaining cultural identity and strengthening social cohesion in villages. Apart from that, this activity also increases spiritual awareness and strengthens traditional values in the midst of modernization. It is hoped that these findings will provide deeper insight into the role of local traditions in today's social and cultural context, as well as serve as a means to introduce the community.